Analysis of Selection Community Knowledge Organic and Inorganic Waste in Silau Village Merawan Dolok Masihul District, Serdang Bedagai - Nanda, Meutia; Sinambela, Nur Delina; Rahmadanty, Dwi Azura; Saragih, Eka Fitria; Sabina, Ramania (PROMOTOR, 2024)
Analysis of the community's knowledge of sorting organic and inorganic waste in Silau Merawan village, Dolok Masihul District, Serdang Bedagai, after carrying out outreach activities, good knowledge can be obtained which has increased by 50%. The aim of this outreach activity is to determine the public's knowledge of sorting organic and inorganic waste. This research method is qualitative in nature where the data collection is primary, with community participation as 30 respondents. The results of the research showed that before providing education to the public, the accuracy rate for good knowledge was only 16.7%, and bad knowledge reached 83.3%. However, after providing counseling to the community, their knowledge increased significantly, where good knowledge reached 50%. Thus, it can be concluded that this counseling is effective so that it can increase public knowledge significantly.